2021
DOI: 10.1007/s12325-021-01658-1
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Chronic Kidney Disease and Estimated Glomerular Filtration Rate Decline in Patients with Chronic Hypoparathyroidism: A Retrospective Cohort Study

Abstract: Introduction: Chronic hypoparathyroidism, treated with conventional therapy of oral calcium supplements and active vitamin D, may increase the risk of kidney complications. This study examined risks of development and progression of chronic kidney disease (CKD) and estimated glomerular filtration rate (eGFR)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
26
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 21 publications
1
26
0
2
Order By: Relevance
“…This can be compared to the results of our study, showing a 3- to 4-fold increased risk of CKD and urolithiasis in both postsurgical and nonsurgical chronic hypoPT. More recently, Gosmanova et al, identified more than 8000 patients with chronic hypoPT on conventional treatment and showed an increased risk of incident CKD (HR 2.91; 95% CI, 2.61-3.25), progression of CKD stage and progression to end-stage kidney disease compared to persons without hypoPT during a 5-year follow-up ( 24 ). Bergenfelz et al showed an almost 5-fold increased risk of CKD in patients with postsurgical hypoPT in Sweden who underwent total thyroidectomy, compared with patients who underwent total thyroidectomy but did not develop postsurgical hypoPT ( 25 ).…”
Section: Discussionmentioning
confidence: 99%
“…This can be compared to the results of our study, showing a 3- to 4-fold increased risk of CKD and urolithiasis in both postsurgical and nonsurgical chronic hypoPT. More recently, Gosmanova et al, identified more than 8000 patients with chronic hypoPT on conventional treatment and showed an increased risk of incident CKD (HR 2.91; 95% CI, 2.61-3.25), progression of CKD stage and progression to end-stage kidney disease compared to persons without hypoPT during a 5-year follow-up ( 24 ). Bergenfelz et al showed an almost 5-fold increased risk of CKD in patients with postsurgical hypoPT in Sweden who underwent total thyroidectomy, compared with patients who underwent total thyroidectomy but did not develop postsurgical hypoPT ( 25 ).…”
Section: Discussionmentioning
confidence: 99%
“…In a study from Denmark, patients with hypoparathyroidism ( n = 688) had an almost fivefold increased risk of renal insufficiency compared with age- and gender-matched controls ( n = 2064) [ 5 ]. A retrospective cohort study from the USA showed that patients with chronic hypoparathyroidism ( n = 8097) had increased risk of developing incident CKD stage 3 or higher, and had increased risk of decline in eGFR ≥ 30% compared with patients without hypoparathyroidism ( n = 40,485) [ 2 ]. Moreover, a study conducted in Scotland identified a higher risk of renal failure, defined as eGFR < 30 mL/min, in patients with chronic hypoparathyroidism ( n = 280) compared with age- and gender-matched controls ( n = 1301) and showed that mean serum calcium concentration was associated with renal failure [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…In some patients, conventional therapy fails to adequately control hypoparathyroidism. Patients remain symptomatic, with episodes of hypocalcemia and hypercalcemia, and may develop complications, including chronic kidney disease (CKD) [1,3,[11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Tis can lead to transient periods of hypercalcemia and hypercalciuria [1,3]. An increasing body of evidence indicates that patients with chronic hypoparathyroidism treated with conventional therapy are at increased risks for nephrolithiasis, nephrocalcinosis, developing a decline in eGFR, and progression to end-stage kidney disease [11,14,[16][17][18][19][20][21][22][23]. However, despite evidence for an association between CKD and hypoparathyroidism, little is known about which factors mediate this association.…”
Section: Introductionmentioning
confidence: 99%